Evaluación de tres métodos de deshije en el cultivo de banano musa sapientum - Ganán Ordóñez, Italo Rolando (2012)
This research work was carried out on the farm of Mr. Nelson Muñoz, located in the Canton ofArenillas, belonging to the province of El Oro About desuckering as an alternative to handle the density of plants and examine their effect on production. The objectives were to evaluate the effects ofroguing in different ages; Determine desuckering higher performance in production and an economic analysis. The test site was located in the formation of a tropical dry forest (bms-T), with a semiarid climate, annual average temperature of 25.3 ° C, with water deficiencies and rainfall of 658 mm. Treatments were: T1. Desuckering at 10 weeks leaving 1 son satellite. T2. Desuckering to children 12 weeks leaving 1 satellite. T3. Desuckering at 10 weeks son leaving 2 satellite. T4. Desuckering at 10 weeks are leaving 2 satellite. The variables were yolk height to 40-90 and calving. Thickness of thepseudostem, number of hands per bunch, bunch weight, bunch and Degree Days to the appearance of buds selected